Karyological Analysisof Red Junglefowl (Gallus gallus gallus Linnaeus, 1758) Using Egg Fibroblastic Cell Culture - พิมพันธุ์, สุมาลี; แทนออมทอง, อลงกลด; ช่วยเงิน, ยอดชาย; ประทุมทอง, โดม (KKU Science Journal, 2015)
This is the first report karyological analysis of the red junglefowl (Gallus gallus gallus) from Thailand. This research aimed to examine karyotypes ofthe red junglefowl. Fibroblastic cells were taken from junglefowl egg and cultured at 41 oC for 24 hr. The cultured fibroblast were then prepared for chromosomes by using the colchicine-hypotonic-fixation-air drying technique and followed by conventional staining and GTG-banding techniques. The results showed that the diploid chromosome number was 2n=78, and fundamental number (NF) were 88 in both male and female. The types of macrochromosomes were 2 large metacentric, 2 large submetacentric, 2 medium telocentric, 2 medium submetacentric, 4 small telocentrics, 4 small metacentrics, and 30 microchromosomes. The Z chromosome was a medium metacentric chromosome, while the W chromosome was the small metacentric chromosome. The GTGbanding technique clearly revealedthe compatible pairs of bands on each of macrochromosome and also showed 139 bands’ number from all of those macrochromosome. The karyotype formula of the junglefowl is as follow: 2n (78) = Lm2+Lsm2+Mt2+Msm2+St4+Sm4 + microchromosomes + sex chromosomes (ZW)